1997
DOI: 10.1071/a96069
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the acidity and fertility of a red earth soil under wheat–annual pasture rotations

Abstract: This paper reports the effects of 6 wheat–annual pasture rotations over 18 years on soil N, organic C, P, and pH in a red earth soil at Wagga Wagga (35° 03′ S, 147° 21′E), in southern NSW. There were 3 cropping intensities (33, 50, 67%) with pastures dominated by subterranean clover (Trifolium subterraneum L. cv. Bacchus Marsh) and annual ryegrass (Lolium rigidum Gaud. cv. Wimmera). Rotations were long (6-year) or short (2- or 3-year). Initial soil N and organic C concentrations (0–10 cm) were low, 1300–1400 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 41 publications
3
38
1
Order By: Relevance
“…These increases were correlated with increased soil organic matter following P fertilisation; a similar result to that observed in a 30 year perennial forestry trial near Sydney (Turner and Lambert 1985). Conversely, Helyar et al (1997) reported that more than half of the P accumulated over 18 years was organic P at a different site near Wagga Wagga, NSW. The contrasting result to that of Bunemann et al (2006) may be due to either lower P additions or the inclusion of pasture phases in the Helyar et al (1997) study.…”
Section: Organic Phosphorus Mineralisation and Immobilisation Reactionssupporting
confidence: 60%
See 1 more Smart Citation
“…These increases were correlated with increased soil organic matter following P fertilisation; a similar result to that observed in a 30 year perennial forestry trial near Sydney (Turner and Lambert 1985). Conversely, Helyar et al (1997) reported that more than half of the P accumulated over 18 years was organic P at a different site near Wagga Wagga, NSW. The contrasting result to that of Bunemann et al (2006) may be due to either lower P additions or the inclusion of pasture phases in the Helyar et al (1997) study.…”
Section: Organic Phosphorus Mineralisation and Immobilisation Reactionssupporting
confidence: 60%
“…Conversely, Helyar et al (1997) reported that more than half of the P accumulated over 18 years was organic P at a different site near Wagga Wagga, NSW. The contrasting result to that of Bunemann et al (2006) may be due to either lower P additions or the inclusion of pasture phases in the Helyar et al (1997) study. Note that Helyar et al (1997) also used the ignition method to determine organic P. Guggenberger et al (2000) found there was little difference in the ratio of P i to P o for soils fertilised with manure compared to those fertilised with similar amounts of mineral P fertiliser.…”
Section: Organic Phosphorus Mineralisation and Immobilisation Reactionsmentioning
confidence: 94%
“…Soil organic matter concentrations are increased during legume-based pasture phases (e.g. Grace et al 1995;Dalal et al 1995;Helyar et al 1997) and nutrients are mobilised from soil organic matter and used during crop phases, bare fallows and continuous cropping (e.g. White et al 1978;Dalal and Mayer 1986;Dalal and Chan 2001;Bünemann et al 2006).…”
Section: Farming Systems That Utilise Soil Organic Pmentioning
confidence: 99%
“…McLaughlin et al 1990;Bünemann et al 2006), but there are relatively few reports of the amounts of P that are accumulated in soil maintained under steady-state P-fertility conditions, where accumulation will be the net result of phosphate sorption/desorption reactions and the slowly cycling components of soil organic matter that release phosphate at rates slower than the rate of P supply necessary for commercial agricultural production. Two long-term experiments: a pasturewheat crop rotation (Wagga Wagga, New South Wales [NSW], Australia; Helyar et al 1997) which accumulated~4.6 kg P ha -1 year -1 (P-balance efficiency~60%), and a permanent pasture (Hall, Australian Capital Territory, Australia; Simpson et al 2010) which accumulated~7.3 kg P ha -1 year -1 when managed at near-optimal P fertility (P-balance efficiency~20%), demonstrate how large the soil P accumulation term of the P-balance equation can be for moderate to highly P-sorbing soils under relatively "stable" soil P-fertility conditions. For accumulation of P to be reduced under these conditions, it would be necessary to shift the balance between phosphate sorption and desorption rates, and/or between the rates of soil organic P input and mineralisation.…”
Section: P-losses (Erosion Runoff and Leaching)mentioning
confidence: 99%
See 1 more Smart Citation